Nilai Spiritualitas Sayyed Hossein Nasr dalam Manajemen Pendidikan Islam - Limas Dodi (Universitas Pesantren Tinggi Darul 'Ulum, 2018)
Starting from the spiritual crisis that befell humans in modern era, the development of Western technology that is not balanced with the value of esoterios makes them crashing. Science that has been worshiped precisely the problem for humans by flowing the flow of globalization and information so powerful even according to Hosen Nasr, science eventually become rulers and dominate nature. The advancement of science and technology, the dominance of rationalism, empiricism and positivism, turns people into a modern life in which secularism becomes the mentality of the times and therefore spiritualism becomes a theme for modern life. Spiritual Based Education is based on the belief that education activity is worship to Allah SWT. Man was created as a holy servant of God and given the mandate to preserve the holiness. In general, spiritual-based education focuses its attention on spirituality as a prime potential for mobilizing every act of education and instruction, in this sense understood as a normative source of inspiration in educational and teaching activities, as well as spirituality as an educational goal. With the application of the concept of spiritualization of education. The integrity between faith and science, reason and religion, heart and mind is one of the models that education can effectively build a whole person. Spiritual leadership is a leadership model that puts forward spiritual values or spirituality to influence, inspire, enlighten and empower those who are led.Nilai Spiritualitas Sayyed Hossein Nasr dalam Manajemen Pendidikan Islam